Trypanocidal failure suggested by PCR results in cattle field samples - Gall, Y.; Woitag, T.; Bauer, B.; Sidibe, I.; McDermott, John J.; Mehlitz, D.; Clausen, Peter-Henning (Elsevier, 2004)
The aim of this study was to assess, whether polymerase chain reaction (PCR) allows sensitive screening of treatment failure suspicions in areas, where drug resistance against African animal trypanosomosis (AAT) appears to be a problem. PCR was used to detect trypanosome infections prior to, 14 and 28 days after controlled treatment of 738 cattle from 10 villages in Kenedougou, Burkina Faso with isometamidium chloride and diminazene aceturate. Using three sets of primers, PCR was three-four times more sensitive and better at species identification, than standard microscopic examination. The better sensitivity and species specificity of PCR have important advantages for drug resistance studies in the field.